Publisher’s Note: A cursory look at Aquaculture in Canada - Ochuko, Tonukari (Advances in Aquaculture and Fisheries Management, 2013)
Aquaculture is the farming of fish, shellfish or aquatic plants in either fresh or saltwater, or both.[1] The farmed animals or plants are cared for under a controlled environment to ensure optimum growth, success and profit. When they have reached an appropriate size (often once they reach maturity), they are harvested, processed, and shipped to markets to be sold.[2] Aquaculture is practiced all over the world and is extremely popular in countries such as China, where population is high and fish is a staple part of their everyday diet.